The Audit Expectation Gap: How Can Auditing Teaching Mitigate It? - Widya Ais Sahla; Nurul Qalbiah; Tino Kemal Fattah (Indonesian Journal of Applied Accounting and Finance, 2021)
This study aims to determine the perceptions of accounting students who have not and who have received auditing teaching on the Audit Expectation Gap. There are several issues in the expectation gap, namely the issue of auditors and the audit process, issues of the role of auditors and issues of competence and auditor independence. This research is a survey to a 115 students of the Accounting Department in State Polytechnic of Banjarmasin, Lambung Mangkurat University, STIENAS and STIEPAN. Based on the independent sample t-test through SPSS 25, the following results were obtained: (1) There are differences in perceptions between students who have not and who have received auditing teaching on the expectation gap in auditor’s issues and the audit process; (2) There is no difference in perception between students who have not and who have received auditing teaching on the expectation gap in the issue of the role of the auditor. (3) There are differences in perceptions between students who have not and who have received Auditing teaching on the expectation gap in issues of competence and auditor independence